Evaluation of Weight Loss Over Time in Cats with Chronic Kidney Disease. (16th August 2016) - Freeman, L.M.; Lachaud, M.‐P.; Matthews, S.; Rhodes, L.; Zollers, B.
Abstract : Background: Thin body condition and weight loss are common in cats with chronic kidney disease (CKD). However, the time course and progression of weight loss before and after diagnosis have not been thoroughly evaluated. Hypothesis/Objectives: To describe weight loss in cats with CKD before and after diagnosis and its relationship to survival. Animals: A total of 569 cats (55.5% females and 44.5% males) with CKD from 6 US veterinary practices for which International Renal Interest Society (IRIS) stage, age, date of CKD diagnosis, and at least two body weight measurements were available. Methods: Body weight measurements were analyzed by time windows and polynomial growth curve analysis. Survival analysis was performed by Kaplan–Meier curves and log‐rank tests. Results: Median age at diagnosis was 14.9 years (range, 5.0–22.8 years). Cats were categorized at diagnosis as IRIS stage 1 (n = 34 [6%]), stage 2 (n = 345 [61%]), stage 3 (n = 141 [25%]), and stage 4 (n = 49 [9%]). Median body weight at diagnosis was 4.2 kg (range, 1.6–9.9 kg). Cats lost a median of 8.9% of body weight in the 12 months before diagnosis, but weight loss was already present 3 years before diagnosis and accelerated after diagnosis of CKD. Cats <4.2 kg at the time of diagnosis had significantly shorter survival time compared to cats ≥ 4.2 kg at diagnosis ( P < .0001). Conclusions and Clinical Importance: Weight loss can be detected in cats before diagnosis of CKD, accelerates after diagnosis, and is associated with shorter survival. Tracking body weight may help clinicians in earlier diagnosis of CKD.